Our lady of darkness : a novel of ancient Ireland - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels., 2002)
Arriving home from a pilgrim voyage, Sister Fidelma is told that her faithful Saxon companion, Brother Eadulf, is under sentence of death for the murder of a sweet maid. She hastens to the capital of Laigin, determined to appeal against his sentence.